Venuloxanthone, a new pyranoxanthone from the stem bark of Calophyllum venulosum - Ismail, A. A.; Ee, Gwendoline Cheng Lian; Daud, S.; Soek, Sin Teh; Mohd Hashim, Najihah; Awang, Khalijah (Taylor & Francis, 2015)
A new pyranoxanthone, venuloxanthone (1), was isolated from the stem bark of Calophyllum venulosum, together with three other xanthones, tovopyrifolin C (2), ananixanthone (3) and caloxanthone I (4), along with two common triterpenes, friedelin (5) and lupeol (6). The structures of these compounds were identified using several spectroscopic analyses which are NMR, GCMS and FTIR experiments.